Common Musculoskeletal Problems A Handbook - Daniels, James; Hoffman, M. Rebecca; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Common Musculoskeletal Problems in Primary Care: A Handbook is an excellent point of care resource for health care providers to better diagnose and treat patients presenting with common musculoskeletal complaints. Each chapter in this book focuses on a specific joint or region and discusses anatomy, red flags, approach to the patient, common clinical presentations and management, and includes a flow diagram to help direct management and follow-up of a patient$1 (Bs problem. A user-friendly approach makes this handbook an ideal reference for medical students, primary care residents, and practicing primary care providers alike.s
Introduction -- The Cervical Spine -- The Shoulder -- The Elbow -- The Hand and Wrist -- The Lumbosacral Spine -- The Hip -- The Knee -- The Ankle -- Common Pediatric Musculoskeletal Problems -- The Acutely Painful, Swollen Joint -- Muscuoloskeletal Radiology -- Splinting and Soft Tissue Issues -- Pre-participation Evaluation -- Appendix.
Keywords: Medicine; Emergency medicine; Medicine & Public Health; Primary Care Medicine